Cadmium acetate induced hematotoxicity, sperm abnormality and mutagenicity in rats - Al-Fartosi, Khalid (University of Thi-Qar Journal of Science, 2010)
Cadmium (Cd) is a dangerous occupational and environmental toxin. The aim of this study is to assess the long – term uptake of cadmium acetate on blood parameter, sperm numbers, sperm abnormality and mutagenic index of male and female rats. Male and femle wistar rats were administrated orally with 200 ppm and 400 ppm cadmium acetate for six weeks. After the end of administration, the animals were anaesthetized and blood samples were collected from their hearts for blood parameters. Right and left epidydimus were collected for study of sperm numbers and sperm abnormality. Mutagenic index of male rats was determined after six weeks of the treatments of male rats with cadmium acetate by mating it with normal female rats. The results showed the significant decreasd of all blood parameters of male and female rats treated with cadmium acetate compared with control group. Sperm concentration was decreased significantly, while sperm abnormality was increased significantly in male rats treated with 200 ppm and 400 ppm cadmium acetate. Mutagenicindex was increased in male rats treated with 200 ppm cadmium acetate compared with control group. No pregnancy was noted when male rats were treated with 400 ppm cadmium acetate mated with normal female rats.